Developing a Supplementary English Grammar Material Using Grammar-Translation Method for Higher Students - lutfiana nur arifah; M. Luthfi Abdillah (FKDP (Forum Komunikasi Dosen Peneliti), 2020)
This research is aimed to develop a supplementary English grammar material for D intensive students at INKAFA Gresik. The researcher used Educational Research and Development, and the procedures are: (1) Need analysis. (2) Planning. (3) Developing material. (4) Evaluating Material. (5) Try-out, the product was tried out to the students. (6) Revising. (7) Final Product. The product consisted of nine chapters. Every chapter consists of three stages; they are Warming-up, lesson proper, and evaluation. The second stage (experience appropriate) consists of three sub-stage. Those three sub-stages are grammar area, vocabularies area, and reading area. The result of expert validation of the book from the expert showed that the product was categorized as useful. Thus, it can be concluded that the outcome of this research has been appropriated for D intensive students